Mass spectrometry-based high-throughput sample treatment methods for analysis of xenobiotics in human biofluids - Esther González-Infante; Anne San Román; Juan F. Ayala-Cabrera; Nestor Etxebarria; Belén González-Gaya; Naroa Lopez-Herguedas; Mikel Musatadi; Maitane Olivares; Ailette Prieto; Olatz Zuloaga (Advances in Sample Preparation)
This review examines recent advancements in high-throughput sample treatment for mass spectrometric analysis of organic xenobiotics in human biofluids. The first section explores emerging techniques using solid, liquid and polymeric sorbents, emphasizing configurations that enhance batch processing and environmental sustainability. Innovations in solid-phase (micro)extraction and liquid-liquid (micro)extraction are discussed, along with advancements in sorbent materials. Additionally, centrifugal-assisted sample treatment is highlighted as a complementary technique that streamlines key steps, including protein precipitation. Special attention is also given to direct infusion and ambient ionization-based mass spectrometry, which significantly reduce analysis time by eliminating chromatographic separation. Automation, crucial for handling large sample volumes in clinical and biomonitoring studies, is also emphasized. The second section reviews recent applications of high-throughput techniques for detecting organic xenobiotics in human biofluids via mass spectrometry. While the primary focus is on urine and blood/plasma/serum, other biofluids such as breast milk, oral fluid, semen and cerebrospinal fluid are also considered. Most studies aim to increase sample throughput via automation, batch processing, or direct analysis, while miniaturization and novel sorbents remain less explored. Research remains largely centered on legal and illegal drug analysis, with fewer studies addressing exogenous xenobiotics such as pesticides, industrial chemicals, or endocrine-disrupting chemicals. Further efforts are needed to develop methods capable of detecting a broad spectrum of compounds within a single workflow. Finally, establishing standardized metrics to quantitatively assess throughput beyond traditional figures of merit is essential for defining high-throughput sample preparation in a meaningful and universally accepted manner.